Pendidikan Kesehatan Reproduksi terhadap Respon Psikologis Remaja Saat Menarche - I Dewa Made Ruspawan; Sur Suratiah (Jurnal Gema Keperawatan, 2015)
The purpose of this study was to determine Influence of Reproductive Health Education to Adolescent Psychological Response in experiencing Menarche at VII Class SMP Negeri 10 Denpasar. This study used pra – experimental with one Group pra Post test Design that involved 20 respondents as sample which chosen by purposive sampling method. The result before provision of health education showed 12 respondent (60%) were in negative response category. And the result after provision health education showed 20 respondents (100%) were in positive response category. The analysis result using wilxocon signed rank test at significant level at p = 0,05 was obtained p = 0,00, it means there is Influence of Reproductive Health Education to Adolescent Psychological Response in experiencing Menarche at VII Class SMP Negeri 10 Denpasar.